Development of self-care in Spanish community pharmacies - Noelia Amador-Fernández; Miguel Ángel Gastelurrutia; Victoria García-Cárdenas (Elsevier, 2023)
Spain is a European country with over 47.5 million inhabitants and a public National Health System model (i.e., SNS or "Sistema Nacional de Salud") that provides universal coverage to residents and non-residents. The system is funded primarily by general taxes, and it is managed by the 17 regions that have responsibility for the provision and management of healthcare services in their respective territories. The health system recognizes self-care as an important element where individuals have an important role to play in maintaining their own health and preventing illness. In addition, there are non-governmental organizations that promote self-care and provide resources and support to individuals and health professionals.Over 55 thousand pharmacists work in 22,198 community pharmacies distributed throughout the Spanish territory. Pharmacies are the only setting that provide non-prescription medications, which is one of the most used tools for self-care. In addition, they provide a range of Primary Care services to improve patient outcomes and the efficiency of the SNS. This paper includes a description and a classification of the community pharmacy services following the seven pillars of self-care established by the International Self-Care Foundation: - Related to pillars 1 to 4 and 6, Spanish community pharmacists provide health promotion, health education, health information and nutritional assessment. - In relation to pillar 5, the services offered are HIV and syphilis screening, colorectal and cervix cancer screening, SARS-CoV-2 screening test and communication, diabetes, high blood pressure and hypercholesterolemia screening. Regarding the programs for avoiding/stopping drug use: methadone supply, syringe exchange and smoking cessation. Another important service is immunization. Spanish community pharmacists are not legally allowed to vaccinate; however, they contribute through education, or vaccines supply, among others. - For the pillar 7, community pharmacists provide services such as a minor ailment service, an adherence service or a network to actively monitor medication safety (sentinel pharmacies). - Many of the pharmacy services related to self-care have been defined and classified at a national level; however, not all community pharmacies provide them while only some services are funded by the regional health systems.